Wildlife of the caribbean coast of Nicaragua / Christopher Jordán - Jordan, Christopher (2009)
Thus, we worked hard to collect local knowledge of and anecdotes about some of the more common, well-known, and locally significant animal species in the RAAS, we then combined this with information available in the scientific literature and information, generated through our own research to create a quide that is both locally relevant and scientifically accurate and educational.